(untitled) - Davide Calamari (Rome, 1994)
It gives advice on strategies for aquatic pollution control, including the establishment of environmental quality standards, emphasizing the use of risk assessment methodologies for arriving at site-specific environmental protection measures. The document further reviews the state of the African aquatic environment in respect of pollution by organic loads, by heavy metals and by organochlorine substances.
Keywords: fisheries